(3TQM JLQjO GdcdGes - (3GdjROj, Ydj Hf GdMSjfs ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3dMUd dUGMHg GdCde HGfbWGYg hGdYbGH dh cGf efbWkYG dMUd dUGMHg GdSQhQ HGfbWGYg ade (B.. (3GdKhGH hGdYbGH NGdUjf Yf ThHs
(3BNQgG (B:s
(3BNQgG(B: (3jhcQg EXgGQ HCKe Efg aQV caGjI dG aQV Yjf aZPG bGe HgG bhe SbW Yf GdBNQjjf, hEPG Xf cd WGFaI Cfg de jbe Hg GdBNQ CKe Gdcd HJQcg(B. (3gPG BNQ eG JjSQ dfG ef TQM JLQjO GdcdGes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds